Analisis Kesulitan Belajar Matematika Materi Pecahan pada Siswa Kelas IV SD Negeri 53 Prabumulih - Dellasari, Dessy; Imansyah, Farizal; Marleni, Marleni (Institut Teknologi Pendidikan Indonesia, 2022)
Many influences as it happens, including lack of interest or lack of pleasure students in learning mathematics, students are less active in the learning process takes place sometimesteachers just explain the material is not interesting and just monotonous. This bias is because at the time of learning the material given is only monotonous should be by using or utilizingexisting media so that students are less active in learning, lack of teachers in mastery of thematerial so that the learning process is less interesting and this becomes one of the mainproblems that cause a lack of interest in students in the learning process Mathematics lastsand causes low and causes students to have difficulty in learning mathematics.